2020
DOI: 10.1186/s12870-019-2218-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific gene expression and protein abundance patterns are associated with fractionation bias in maize

Abstract: Background: Maize experienced a whole-genome duplication event approximately 5 to 12 million years ago. Because this event occurred after speciation from sorghum, the pre-duplication subgenomes can be partially reconstructed by mapping syntenic regions to the sorghum chromosomes. During evolution, maize has had uneven gene loss between each ancient subgenome. Fractionation and divergence between these genomes continue today, constantly changing genetic make-up and phenotypes and influencing agronomic traits. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Next, we analyzed the protein abundance using publicly available data from 148 samples of 23 tissues with the same cutoff as that for RNA expression ( Walley et al 2016 ; Walsh et al 2020 ). In all the four categories, maize1 dominates protein abundance in most of the samples ( supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we analyzed the protein abundance using publicly available data from 148 samples of 23 tissues with the same cutoff as that for RNA expression ( Walley et al 2016 ; Walsh et al 2020 ). In all the four categories, maize1 dominates protein abundance in most of the samples ( supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the pollen classifiers consistently performed significantly worse than any other tissue across all experiments. Other studies including (Walsh et al, 2020) have shown that as compared to other tissues, maize pollen has fewer expressed genes, a higher rate of expressed transcription factors, and that pollen mRNA abundance has low correlation with protein abundance. The same study showed that out of the same 23 tissues only "pollen" and "endosperm crown 27 days after pollination" had higher expression in the non-dominant subgenome of maize.…”
Section: The Two-phase Methods Could Reliably Identify Genes With Hig...mentioning
confidence: 96%
“…The original expression data was from the gene expression tissue atlas data (Walley et al, 2016). The data was remapped to B73 RefGen v4 (Jiao et al, 2017) by (Walsh et al, 2020) and downloaded from MaizeGDB (Portwood et al, 2019). Each gene had 23 value pairs of tissuespecific RA and PA data.…”
Section: Datamentioning
confidence: 99%
“…It is worth noting the pollen classifiers consistently performed significantly worse than any other tissue across all of our experiments. Other studies including (Walsh et. al, (Walsh et al, 2020)) have shown that as compared to other tissues maize pollen has fewer expressed genes, a higher rate of expressed transcription factors, and that mRNA abundance has low correlation with protein abundance.…”
Section: The Two-phase Methods Could Reliably Identify Genes With High Expression In Most Tissuesmentioning
confidence: 99%
“…The original expression data is from the gene expression tissue atlas data . The data was remapped to B73 Refgen v4 by (Walsh et al, 2020) and downloaded from MaizeGDB (Portwood et al, 2019). Each gene has 23 values of RA and PA data which correspond to each tissue.…”
Section: Datamentioning
confidence: 99%